The DCDC2/ENO1 axis promotes tumor progression and immune evasion in intrahepatic cholangiocarcinoma via activating FGL1-LAG3 checkpoint - Wenze Wan; Yuan Li; Wentao Sun; Zewei Cheng; Fen Ma; Sheng Shen; Houbao Liu; Jiwei Zhang (Journal of Experimental & Clinical Cancer Research)
Abstract Background & Aims ICC is a malignant tumor that originates from the intrahepatic bile ducts with insidious symptoms and a poor prognosis. Early diagnosis methods and therapeutic targets are urgently needed for ICC. Methods We utilized a comprehensive set of analytical techniques to elucidate the role and mechanisms of DCDC2 in ICC. Our study included protein microarrays, transcriptome analysis, functional assays, immunofluorescence, dual-luciferase reporter assays, as well as xenograft models and humanized PBMC models. Results Our study demonstrates that elevated levels of anti-DCDC2 autoantibodies in the serum of ICC patients indicate its potential utility as a diagnostic biomarker. Comprehensive in vitro and in vivo analyses reveal that DCDC2 promotes ICC proliferation, metastasis, and immune evasion. Mechanistically, DCDC2 stabilizes ENO1, resulting in enhanced AKT phosphorylation and increased expression of FGL1. Notably, elevated FGL1 levels significantly impair CD8+ T cell functionality via the FGL1-LAG3 axis. Conclusion Our findings position anti-DCDC2 autoantibody as a promising diagnostic biomarker for ICC, associated with poor prognostic outcomes, and elucidate its critical role in tumor growth and immune evasion through its interaction with ENO1.